2017
DOI: 10.1038/srep44105
|View full text |Cite
|
Sign up to set email alerts
|

A potential and novel type transgenic corn plant for control of the Corn Borer

Abstract: The corn borer is a world-wide agricultural pest. In this study, a full-length neuropeptide F (npf) gene in Ostrinia furnacalis was sequenced and cloned from a cDNA library, in which the npf gene produces two splicing mRNA variants - npf1 and npf2 (with a 120 bp segment inserted into the npf1 sequence to generate npf2). A spatio-temporal expression analysis showed that the highest expression level of npf was in the midgut of 5th instar larvae (the gluttony period), and their npf expression and food consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Thus, silencing the target gene NPF not only inhibited their expression levels but also resulted in augmentation of mortality in the state of both starvation and feeding. The result was consistent with previous studies on H. armigera; the NPF RNAi led to high mortality of this species, in which all animals could not pupate or emerge due to abnormal growth and development (Yue et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, silencing the target gene NPF not only inhibited their expression levels but also resulted in augmentation of mortality in the state of both starvation and feeding. The result was consistent with previous studies on H. armigera; the NPF RNAi led to high mortality of this species, in which all animals could not pupate or emerge due to abnormal growth and development (Yue et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Feeding behavior provides more nutrients to reduce the metabolic demands of stored glycogen and free fatty acid. This pattern was consistent with H. armigera and Ostrinia furnacalis, and in contrast to O. furnacalis, downregulated NPF causes a decrease of free fatty acid in D. armandi instead of total lipid (Yue et al, 2016(Yue et al, , 2017, suggesting that the NPF system is involved in insulin signal to regulate energy metabolism, which is a hypothesis that needs to be further investigated.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, research on the function of NPF showed that they have important roles in regulating the feeding behavior of insects, especially in resisting noxious food (Li et al, 2018;Tan et al, 2019;Van Wielendaele et al, 2013;Wu, Zhao, et al, 2005). These findings raised its potential application in pest control (Yue et al, 2017(Yue et al, , 2016. However, the possible roles of NPFs in Cry toxins induced feeding inhibition have not yet been reported, even though at the early stage of the larvae feeding on Bt-transgenic crops or Bt toxins incubated diet, notable feeding inhibition always be observed by quantifying the relative amount of frass produced (Choi et al, 2008).…”
Section: Synergistic Effects Of P X-npf On Cry1ac Toxicitymentioning
confidence: 99%
“…Currently, novel approaches direct attention to neuropeptides, which may address the existing and increasing problems with the evolution of resistance in insect populations via regulating insect physiology and behavior (Nässel & Zandawala, 2019). H. armigera and Ostrinia furnacalis larvae which were fed on transgenic dsNPF plants or directly injected dsNPF had lower food consumption, body size, and body weight compared to controls (Cui et al, 2020;Yue et al, 2017Yue et al, , 2016. These results indicate that NPF is important in the control of feeding of pest larvae and valuable for the production of potential transgenic crops.…”
Section: Introductionmentioning
confidence: 99%
“…NPF was first identified in Helicoverpa zea [6], followed by Drosophila melanogaster [7], Schistocerca grearia [8], Aedes aegypti [9], Anopheles gambiae [10], Locusta migratoria [11], Bombyx mori [12], Reticulitermes flavipes [13], and Helicoverpa assulta [14]. One important function regulated by NPF is feeding behaviour, which has been reported in invertebrates [15] and in many insects, such as D. melanogaster [16], Heliothis assulta [14], Helicoverpa armigera [17], Acyrthosiphon pisum [18], L. migratoria [19], Grapholita molesta [20], Ostrinia furnacalis [21][22][23][24], etc. We previously reported that NPF is mainly expressed in the larval midgut and brain in H. assulta [14], H. armigera [17], and O. furnacalis [21,22].…”
Section: Introductionmentioning
confidence: 99%